2023
DOI: 10.1002/anie.202301956
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Catalytic Systems for Chemical Energy Conversion

Abstract: The rapidly growing importance of green hydrogen and renewable carbon resources as essential feedstocks for sustainable chemical value chains opens room for disruptive innovations regarding chemical production processes. The fluctuation and variability associated with non‐fossil energy and raw material supply holds many challenges for catalysts to cope with the resulting dynamics. However, many new opportunities also arise once catalyst design starts to aim at performance that is “adaptive” rather than “task‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Finally, we demonstrated that the activity of the catalyst can be reversibly toggled between two states, by subsequently adding fluoride or [NO + ](BF 4 − ). Overall, all these characteristics qualify our system to fit within the recently defined category of ‘adaptive catalytic systems’, as it is capable of being adjusted into different states of performance in a reversible, rapid and robust manner [23] …”
Section: Discussionmentioning
confidence: 93%
“…Finally, we demonstrated that the activity of the catalyst can be reversibly toggled between two states, by subsequently adding fluoride or [NO + ](BF 4 − ). Overall, all these characteristics qualify our system to fit within the recently defined category of ‘adaptive catalytic systems’, as it is capable of being adjusted into different states of performance in a reversible, rapid and robust manner [23] …”
Section: Discussionmentioning
confidence: 93%
“…Overall, all these characteristics qualify our system to fit within the recently defined category of 'adaptive catalytic systems', as it is capable of being adjusted into different states of performance in a reversible, rapid and robust manner. [23] ). The reaction was carried out in CD 3 CN at 80 °C, with an initial concentration of 4-pentynoic acid of 0.33 M. Product yields determined by 1 H NMR spectroscopy using 1,3,5-trimethoxybenzene as an integration standard.…”
Section: Discussionmentioning
confidence: 99%
“…During the past three decades, the use of catalysts with ligands that incorporate stimulus-responsive units has appeared as an efficient way of conferring a biomimetic level of control over chemical transformations . Such level of control allows the tuning of the catalyst for specific needs and therefore can be used to enable chemical transformations that are difficult to achieve by other means.…”
Section: Introductionmentioning
confidence: 99%